Reuse of honey jars for healthier bees: Developing a sustainable honey jars supply chain through the use of LCA. (10th March 2018) - Postacchini, Leonardo; Mazzuto, Giovanni; Paciarotti, Claudia; Ciarapica, Filippo E.
Abstract: This study aims at improving the environmental sustainability of an existing honey production supply chain, pursuing the Sustainable Supply Chain Management philosophy and the Life Cycle Assessment principles. Focusing the attention on the packaging stage and, in particular, on the most commonly used honey packaging solution, the glass jar, this study assesses the environmental burdens associated with its manufacturing, distribution and final disposal. Once the "AS-IS" honey packaging situation of an Italian province has been analyzed, parallel packaging reuse scenarios and redistribution supply chains are modelled, involving different levels of collaboration between the honey producers and the provincial beekeeping consortium. These scenarios have been then compared to the AS-IS situation, taking into account five environmental factors important for the honeybee's survival: the carbon dioxide equivalent emission, the triethylene glycol equivalent emissions into water and soil, the sulfur dioxide equivalent emission into air and the m 2 equivalent reduction of organic arable land per year. The outcomes show how the adoption of a packaging reuse policy together with a producer collaboration policy could bring, in five years, to reduce those factors on average of 16% (with a 10% packaging reuse rate), up to more than 70% (with an 85% packaging reuse rate). Graphical abstract: Highlights: Analysis of an existing honey production Supply Chain (SC) in an Italian province. Packaging reuse and logistic optimization to model alternative honey jars SCs. LCA comparison of the different modelled jars SCs to the existing one. Emissions reduction, in 5 years, of 16% (with a 10% packaging reuse rate). Emissions reduction, in 5 years, up to 70% (with an 85% packaging reuse rate).